Nutrient Management for Sustaining Productivity of Sunflower-Based Cropping Sequence in Indian Semiarid Regions. Issue 5 (9th March 2017) - Sheoran, Parvender; Sardana, Virender; Singh, Sher; Chander, Subhash; Kumar, Ashwani; Mann, Anita; Sharma, Pushp
ABSTRACT: A comprehensive long-term study (2006–2010) was undertaken to develop a balanced and integrated nutrient supply system for sunflower-based cropping sequence considering the efficient utilization of residual and cumulative soil nutrient balance along with added fertilizers by the crops grown in rotation. The fertilizer application was done in potato and sunflower while greengram was raised as such on their residual effect. Significant response in yield was observed with 150% of the recommended nitrogen, phosphorus and potassium (NPK) or inclusion of farmyard manure (FYM) with the recommended NPK in the cropping sequence indicating 6.2–7.0% gain in system productivity over the existing recommendations. Each additional unit of P and K nutrition prompted system productivity by 18.9 and 11.0 kg kg −1 of applied nutrient, respectively. Apparent yield decline was observed in K and PK omission plots to the extent of 15.8 and 27.4% in potato, 10.5 and 23.9% in sunflower and 4.2 and 8.3% in greengram, respectively, compared to the recommended fertilization. The superiority of the FYM along with the recommended NPK (potato/sunflower) was evident on the overall profitability and sustainability of the system, highlighted by the significantly higher productivity (7.16 t SFEY ha −1 ), sustainability yield index (SYI; 0.76), production efficiency (PE; 27.85 kg SFEY ha −1 day −1 ) and net returns (2520 USD ha −1 ) with a B:C ratio of 2.91. Apparent change in potassium permanganate (KMnO4 )-N was negative in all the treatments while N and P balance was positive with 150% NPK fertilization. Nutrient uptake exceeded the replenishment with 100% NPK application and maintained net negative soil nutrient stock for all the primary nutrients, indicating the need for revalidation of the existing recommendations in the system perspective. Conspicuous improvement in residual soil fertility in terms of maximum buildup of soil organic carbon (14%) and enhancement in soil KMnO4 -N (4.2%), Olsen-P (19.4%), ammonium acetate (NH4OAc)-K (5.8%) and dehydrogenase enzyme activity (44.4%) was observed in FYM-treated plots over the initial values. The study suggested that the inclusion of legumes and FYM application with the recommended NPK in potato-sunflower cropping sequence will sustain the system's productivity through the efficient use of nutrients, enhanced microbial activity and improved soil health while combating escalating prices of fertilizers as well as environmental issues in the Indo-Gangetic plains of India and similar environments.